2011
DOI: 10.1007/s13369-011-0117-x
|View full text |Cite
|
Sign up to set email alerts
|

A Classification of Refactoring Methods Based on Software Quality Attributes

Abstract: Refactoring is the process of improving the design of existing code by changing its internal structure without affecting its external behavior. Refactoring tends to improve software quality by improving design, improving readability and reducing 'bugs'. There are many different refactoring methods, each having a particular purpose and effect. Consequently, the effect of refactoring methods on software quality attributes may vary. Moreover, it is often unclear to software designers how to use refactoring method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Remediation is prescribed as primarily grammatical or structural often amenable to formulaic manipulations that may be automated in code editors or IDE's [13,25]. The four non-structural exceptions are instances where refactoring actions apply "naming" or "renaming" of code elements to clarify or signify the programmer's motivation; these refactorings incorporate knowledge of the purpose of the code that cannot be gleaned from the source code alone in either the activity of recognition or remediation.…”
Section: "Bad Smells" As Design Quality Deficitmentioning
confidence: 99%
“…Remediation is prescribed as primarily grammatical or structural often amenable to formulaic manipulations that may be automated in code editors or IDE's [13,25]. The four non-structural exceptions are instances where refactoring actions apply "naming" or "renaming" of code elements to clarify or signify the programmer's motivation; these refactorings incorporate knowledge of the purpose of the code that cannot be gleaned from the source code alone in either the activity of recognition or remediation.…”
Section: "Bad Smells" As Design Quality Deficitmentioning
confidence: 99%
“…• Data Abstraction Coupling (DAC): This metric measures the number of instantiations of other classes within a single class (Elish and Alshayeb, 2011) DAC = number of ADTs defined in a class. ADT's refer to abstract data types.…”
Section: Impact Of Code Metrics On Pairingmentioning
confidence: 99%
“…Further research by Dandashi revealed that complexity and LOC were found to be directly proportional to indirect software quality attributes, while NOC, DIT, RFC, and CBO are inversely proportional to indirect software quality attributes. (Dandashi, 2002) C. More Empirical Results of Refactoring -the Elish and Alshayeb Study (Elish, 2011) Elish's study is very significant as it expanded the work by Dandashi by taking code components, measuring their internal directly measurable metrics (based upon Dandashi's metrics) and then performing nine different refactoring activities on that code. After refactoring activities, he then re-analyzed a number of software metrics to note any changes due to the refactoring.…”
Section: Empirical Studies In Refactoringmentioning
confidence: 99%